2007
DOI: 10.1016/j.puhe.2006.09.025
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal comparative study of the physical and mental health problems of affected residents of the firework disaster Enschede, The Netherlands

Abstract: Conclusions: Although health problems decreased compared with 3 weeks after the disaster, 18 months after the disaster, the affected residents had more health problems than the people from the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 24 publications
2
19
0
1
Order By: Relevance
“…those of van der Velden et al (2013), which indicated that residents of the Enschede fireworks disaster were more likely to suffer from sleep problems than controls, 10 years post-disaster. The majority of studies assessing sleep problems in the first years after disasters have also indicated an increased risk of sleep problems in survivors (Chae, Tong Won, Rhee, & Henderson, 2005;Donker, Yzermans, Spreeuwenberg, & Van der Zee, 2002;Grievink et al, 2007). Using the same sleep measurement tools as in our study, Tempesta, Curcio, De Gennaro, and Ferrara (2013) showed that earthquake survivors had higher incidence of sleep impairment and disruptive nocturnal behaviors common to PTSD than inhabitants of surrounding areas 2 years post-disaster.…”
Section: Tablesupporting
confidence: 55%
“…those of van der Velden et al (2013), which indicated that residents of the Enschede fireworks disaster were more likely to suffer from sleep problems than controls, 10 years post-disaster. The majority of studies assessing sleep problems in the first years after disasters have also indicated an increased risk of sleep problems in survivors (Chae, Tong Won, Rhee, & Henderson, 2005;Donker, Yzermans, Spreeuwenberg, & Van der Zee, 2002;Grievink et al, 2007). Using the same sleep measurement tools as in our study, Tempesta, Curcio, De Gennaro, and Ferrara (2013) showed that earthquake survivors had higher incidence of sleep impairment and disruptive nocturnal behaviors common to PTSD than inhabitants of surrounding areas 2 years post-disaster.…”
Section: Tablesupporting
confidence: 55%
“…The PTSD symptoms were found to co-occur with depressive symptoms (Grievink et al, 2007;Reijneveld et al, 2003).…”
mentioning
confidence: 99%
“…Experiencing a fire can be highly stressful (Grievink et al, 2007;Jenkins, Hsu, Sauer, Hsieh, & Kirsch, 2009) but there is a paucity of research examining factors associated with psychological distress in representative community samples. The few studies that do look at psychological outcomes focus on specific groups including college students, children and adolescents, mental health services clients, and firefighters (Bryant & Harvey, 1996;McDermott, Lee, Judd, & Gibbon, 2005;McFarlane, 1987;Scher & Ellwanger, 2009;Tally, Levack, Sarkin, Gilmer, & Groessl, 2013).…”
Section: Introduction and Purposementioning
confidence: 99%